2015
DOI: 10.1038/nature16151
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of fat-resident Treg cells prevents age-associated insulin resistance

Abstract: Age-associated insulin resistance (IR) and obesity-associated IR are two physiologically distinct forms of adult onset diabetes. While macrophage-driven inflammation is a core driver of obesity-associated IR1–6, the underlying mechanisms of the obesity-independent yet highly prevalent age-associated IR7 are largely unexplored. Comparative adipo-immune profiling (AIP) reveals that fat-resident regulatory T cells, termed fTregs, accumulate in adipose tissue as a function of age, but not obesity. Supporting the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
276
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(296 citation statements)
references
References 40 publications
15
276
2
3
Order By: Relevance
“…57 A recent paper reported decreased glucose utilization by expansion of adipose tissue Treg cells in age-associated insulin resistance; however, such findings may not be relevant in obesity-associated insulin resistance. 58 …”
Section: Discussionmentioning
confidence: 99%
“…57 A recent paper reported decreased glucose utilization by expansion of adipose tissue Treg cells in age-associated insulin resistance; however, such findings may not be relevant in obesity-associated insulin resistance. 58 …”
Section: Discussionmentioning
confidence: 99%
“…We also were limited in our inability to fully characterize local mucosal immunological responses, as immunosenescence is present in aged vervet monkeys and is an important phenotype of older people (Haberthur et al, 2010). Immune suppression within mesenteric adipose tissue, and resultant loss of remodeling capacity, has been proposed as an age-related change that results in decreased intestinal barrier function and insulin resistance in rodent models (Wernstedt Asterholm et al, 2014;Bapat et al, 2015). It is possible that waning mucosal immunity and consequential gut leakiness with aging may be offset with moderate exercise as has been seen in rodents (Oliveira et al, 2011), which has implications for clinical geriatricians and physicians managing older patients.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamical model and simulations provide a system-level analytical framework underlying observed cell behaviors and offer predictions that will require experimental validation [ Table 2]. Overall, our simulation study provides a platform to explain the relationship between hyperinsulinemia and altered stability and proportions of T regulatory cells that have been observed in adipose tissue [3,[36][37][38]40]. It also highlights and provides a dynamic explanation for the different roles of TGFβ and IL-10 [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…While TGFβ is present in adipose tissue, its role in regulating Treg cells is still unclear, because the typical alterations caused by TGFβ are not observed in these cells [39]. Paradoxically, it has been reported that the reduction of adipose tissue Treg cells seems to both, improve and worsen insulin resistance [37][38][39][40]. This kind of behavior could be linked to an underlying multi-stable dynamic mechanism such as that recently proposed to study CD4+ T cell differentiation and plasticity [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation